2014
DOI: 10.1039/c4sm00875h
|View full text |Cite|
|
Sign up to set email alerts
|

A generalized method for alignment of block copolymer films: solvent vapor annealing with soft shear

Abstract: One of the key issues associated with the utilization of block copolymer (BCP) thin films in nanoscience and nanotechnology is control of their alignment and orientation over macroscopic dimensions. We have recently reported a method, solvent vapor annealing with soft shear (SVA-SS), for fabricating unidirectional alignment of cylindrical nanostructures. This method is a simple extension of the common SVA process by adhering a flat, crosslinked poly(dimethylsiloxane) (PDMS) pad to the BCP thin film. The impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 55 publications
3
89
1
Order By: Relevance
“…25 Shear flow has also been shown to improve the alignment and uniformity of BCP thin films. 26,27 Molecular dynamics simulations of BCPs under shear flow have investigated the transition between the parallel and perpendicular morphologies 28,29 as well as the placement of NP within lamellar BCP domains. 16 Under extensional flow, Kim et al experimentally studied poly(styrene-co-acrylonitrile) blended with poly methyl methacrylate but was unable to reach steady state.…”
Section: Introductionmentioning
confidence: 99%
“…25 Shear flow has also been shown to improve the alignment and uniformity of BCP thin films. 26,27 Molecular dynamics simulations of BCPs under shear flow have investigated the transition between the parallel and perpendicular morphologies 28,29 as well as the placement of NP within lamellar BCP domains. 16 Under extensional flow, Kim et al experimentally studied poly(styrene-co-acrylonitrile) blended with poly methyl methacrylate but was unable to reach steady state.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated SS‐LZA sweeps effectively impose an oscillatory shear history on the sample, where an internal stress field is repeatedly generated and relaxed. For typical SS‐LZA processing of PS‐b‐PMMA films, uniaxial alignment throughout the entire sample could be achieved in ≈0.3 s, with quality of ordering saturating within ≈20 s. Interestingly, while previous SS annealing studies suggested that excessive shear rates could decrease the quality of BCP alignment due to insufficient time for material response, SS‐LZA demonstrated that BCP films can respond to mechanical stresses even within millisecond timescales (18 ms) due to the large shear rates and high local temperatures.…”
Section: Discussionmentioning
confidence: 96%
“…Because the SVA process can readily control the orientation of self‐assembled BP domains through the appropriate choice of solvents, swollen film thickness, deswelling rate, and vapor pressure, parallel and perpendicular orientations of self‐assembled morphologies are achievable from a diverse array of BP systems. Additionally, SVA can effectively reduce T g and enhance the chain mobility of polymer blocks, while also mitigating the slow diffusion kinetics of higher‐ χ BPs during the self‐assembly process to a much greater extent than thermal annealing . Recently, Vogt and coworkers reported a modified SVA approach that showed the directional alignment of BP thin films through the application of shear during solvent annealing, termed solvent vapor annealing with soft shear (SVA‐SS) .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, SVA can effectively reduce T g and enhance the chain mobility of polymer blocks, while also mitigating the slow diffusion kinetics of higher‐ χ BPs during the self‐assembly process to a much greater extent than thermal annealing . Recently, Vogt and coworkers reported a modified SVA approach that showed the directional alignment of BP thin films through the application of shear during solvent annealing, termed solvent vapor annealing with soft shear (SVA‐SS) . The swelling and deswelling of a soft poly(dimethylsiloxane) (PDMS) pad generated a macroscopic shear stress that could directionally align BP thin film morphologies as the films were drying.…”
Section: Introductionmentioning
confidence: 99%